Class Absenteeism in Pediatrics and Its Impact on Performance: An Analytical Study on under Graduate Students of a Medical College in Dhaka - Shabuj, Mohammad Kamrul Hassan; Shaha, Chandan Kumar (Bangladesh Journal of Child Health, 2017)
Background: Absenteeism in clinical classes is a risk for poor performance in the examinations. But how much performance is affected by each absence in pediatrics? In our study we want to predict this assumption. Methods: The impact of tutorial and clinical class attendance on under graduate students academic performance was investigated based on students average total score and average of frequency of class absence. Total 310 students placed in Medicine and Paediatrics Department of Sir Salimullah Medical College in different time was randomly selected. Results: There is a significant number of pass if ?75% attendance in the class both in medicine and pediatrics. There is a negative correlation between class absenteeism and students performance in the examination. It is predicted that each 10% increase in students absence decrease examination performance by about 4 points in medicine 3 points in pediatrics. Conclusion: More than 75% class attendance is significantly required to score 60 % (passing mark) in the examination. Class absenteeism in pediatrics has the similar effect in performance like that of the medicine that is decreasd in examination performance by about 4 points in medicine, 3 points in Pediatrics for each 10% of absence. Bangladesh J Child Health 2015; VOL 39 (2) :69-72